Arabic Proverbs and Their Historical Significance in Arab-Islamic Thought - Rahim , Majeed Wahib (Thi Qar Arts Journal, 2024)
This research addresses the significance of Arabic proverbs in Arab-Islamic thought, specifically their historical characteristics such as brevity, density of meaning, continuity, the proverb’s origin and context, and the metaphorical relationship between them, as well as strangeness and narrative transmission. It also explores proverbial expressive forms, hyperbolic and exaggerated phrases, ready-made traditional expressions, wisdom, rare sayings, figurative expressions, famous sayings, nominal proverbial formulations, prophetic sayings, Quranic proverbs, and the characteristics of each. Additionally, the proverbs reveal clear indications about the life of the Arab nation, especially in Arab-Islamic thought, as they uncover the nature of this life and clarify many of its aspects that other activities such as poetry and prose did not address.